Aspek Psikologi Tokoh Utama dalam Novel Sang Pemimpi Karya Andrea Hirata - Agus Yulianto (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2017)
The purpose of this study is to understand the form of inner conflict in the main characters and positive messages the author shared. The problem of this research is how the form of inner conflict of the main character and what positive messages the author shared. This study uses analytical descriptive methodology. Based on the results of the analysis, it showed that the inner conflict of the main character is a medium of the writer to convey the author’s positive messages to the readers. It is primarily concerned with the inner conflict of moral and pessimistic the main character feels for the success of a struggle that should not have existed.